I nuovi giardini e i rendering delle agenzie immobiliari. Perché il Nordest Italiano (non?) è la California del Sud - Borelli, Guido (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The new gardens and the real estates rendering. Why Italian Northeast is (not?) the South California. The essay intends to update the reflection on the model of social and territorial development of the Italian Northeast in the last fifty years, making explicit reference to Los Angeles. Although different from each other, the two conurbations show memberships that make the operation not wholly eccentric. One possible way to explore these properties is to resort to different and heterogeneous explanatory sources, privileging among them the literary production that accompanied and, in some cases, guided the construction of the imaginary and of reality in the Northeast and in Los Angeles. In this essay, Los Angeles is used as a figure of speech: a synecdoche that associates two different realities, considers them dependent and logically contiguous, frequently replacing the naming of one to that of the other. Therefore, in the case of this essay, even when we speak of Los Angeles, the reference - even if not explicit - will be the Northeast.